Analisis Faktor-Faktor Yang Mempengaruhi Peringkat Obligasi Pada Perusahaan Keuangan Yang Terdaftar Di BEI Tahun 2012-2014 - Reyssent, Dhea; Kurnia, Ratnawati (Universitas Multimedia Nusantara, 2016)
The goal of this research is to examine the effect of Profitability which proxied by Return on Asset, Leverage which proxied by Debt to Equity Ratio, Cash Flow to Debt Ratio which proxied by Operating Cash Flow to Debt Ratio, Liquidity which proxied by Current Ratio, and Growth which proxied by Market to Book Ratio both partially and simultaneously towards Bond Rating. The objects of this study are financial institution which issuing bonds and rated by PT PEFINDO for 2013-2015, and listed at Indonesia Stock Exchange for the period 2012-2014. Total sample in this research is 20 companies that selected by purposive sampling. The data used in this research is financial statement as secondary data and list of bond rating by PT PEFINDO and analyzed by multiple linear regression. The result of this research indicates that Profitability, Leverage, Cash Flow to Debt Ratio, Liquidity, and Growth simultaneously have a significant effect towards Bond Rating. Liquidity which proxied by Current Ratio had a significant effect to bond rating. Profitability which proxied by Return on Asset, Leverage which proxied by Debt to Equity Ratio and Cash Flow to Debt Ratio which proxied by Operating Cash Flow to Debt Ratio, and Growth which proxied by Market to Book Ratio had no significant effect towards bond rating. Keywords: Bond Rating, Cash Flow to Debt Ratio, Growth, Leverage, Liquidity.